Traffic light system design on FPGA - Boon, Kiat Koay; Mohd. Isa, Maryam (IEEE, 2009)
Traffic light system gives sign of direction and warning to road user to avoid road collision and to optimize the flow rate of vehicle in the junction. This paper presents design of a low cost performance traffic light system. This type of traffic light is suitable for town and small city where sophisticated traffic light system is too costly. A traffic light system nearby the university was chosen as reference. The program is written in verilog on Quartus II software and implemented on DEII FPGA board.